Augmenting agricultural IoT networks: implementing Reed-Solomon codes for Rotating Polarization Waves over LPWAN in Rician fading environments - Ali, Muhammad Moazzam; Hashim, Shaiful Jahari; Chaudhary, Muhammad Akmal; Ferré, Guillaume; Rokhani, Fakhrul Zaman; Ahmad, Zaid (Elsevier, 2025)
This study investigates the integration of Reed-Solomon (RS) codes with Rotating Polarization Wave (RPW) communication to enhance communication reliability in Low-Power Wide-Area Networks (LPWAN) for agricultural IoT applications. The proposed system addresses need for reliable communication under fading conditions in rural settings. RS-coded RPW is evaluated in both ground-to-ground (G2G) and ground-to-drone (G2D) communication scenarios under Additive White Gaussian Noise (AWGN) and Rician fading conditions with emphasis error correction capability and Bit Error Rate (BER) performance. For G2G communication under AWGN conditions, RS coding achieves a BER of 10−4 at Eb/No for number of polarization samples (Np) =5 and 10−5 at Eb/No for Np=7 respectively, demonstrating significant improvement in error correction compared with uncoded RPW. G2D communication shows slightly better performance, achieving 10−4 BER at Eb/No and 10−5 at Eb/No, attributed to the advantage of line-of-sight (LoS) and reduced ground level interference compared with G2G. Under Rician fading, both communication scenarios exhibit increased BER due to multipath interference, with RS-coded systems achieving a BER of 10−3 at 10 dB for Np=5 and 10−4 at 10 dB for Np=7. G2D communication maintains similar BER performance, with 10−3 achieved at 9 dB for Np=5 and 10−4 at 9 dB for Np=7. These results demonstrate the robustness of RS-coded RPW in mitigating errors in both static and dynamic agricultural environments. The integration of RS coding and RPW transmission ensures consistent performance across fading conditions while providing reliable, scalable, and energy efficient communication for precision agriculture. By addressing the unique challenges of rural IoT deployments, the proposed system contributes to the reliability and robustness of LPWAN solutions tailored for large-scale agricultural applications.